Dates (Phoenix Dactylifera) and Date Vinegar: Preventive Role against Various Diseases and Related in Vivo Mechanisms. Issue 4 (19th May 2022) - Ali, Zeshan; Li, Jianke; Zhang, Yuhuan; Naeem, Naureen; Younas, Shoaib; Javeed, Farah
ABSTRACT: Date palm is a useful traditional medicinal plant that is mainly popular for its fruit as the edible portion of the plant. Nowadays, date palm is considered a reliable source of herbal medicine for the management of several diseases. Date palm has been acknowledged for its beneficial properties, such as hepatoprotective, antihyperlipidemic, and antioxidant activities. However, there is a dearth of research exploring the advantages and in vivo mechanisms of date fruit and its by-products, particularly date vinegar. Regarding this, the aim of the current review study was to highlight the role of the phytochemical composition of date fruit and its vinegar in the treatment of various diseases in both acute and chronic conditions, as well as exploring their in vivo mechanisms and nutritional value.